The Mediterranean dish : simply dinner : 125 easy Mediterranean diet-inspired recipes to eat well and live joyfully - Karadsheh, Suzy; Miller, Summer (Clarkson Potter/Publishers, 2024)
"Mediterranean diet-friendly dinners are tastier, healthier, and easier than ever with this new cookbook of 120 fresh and hearty sheet pan, one-pot, and mezze mix-and-match meals from the bestselling author of The Mediterranean Dish. In her first cookbook, The Mediterranean Dish, Suzy Karadsheh shared 120 recipes inspired by her childhood in Egypt, her husband's Palestinian mother, and the comfort food of her new home in Atlanta. In her second book, It's Simply Dinner, Suzy adds another 120 recipes to her repertoire for nutritious Mediterranean diet-inspired meals that not only taste delicious but are so easy to get on the table. Each chapter hones in on a different save-the-day technique, like the magic of one pot cooking (Chermoula and White Bean Chicken Chili), efficient sheet pan suppers (Za'atar-Baked Halibut with Baby Potatoes and Artichoke Hearts); and fast and lean grilling (Grilled Hanger Schwarma over Herby Tomato Salad). Skillet meals, supper salads, and mix-and-match mezze abound, along with a section devoted to protein add-ons in case you just want to add some quick skillet shrimp to a Barley and Red Bean Salad with Mint and Hazelnut and call it a day. Both new fans and devoted ones will turn to this hard working cookbook, with more than 120 photos, again and again as they cook up Suzy's delightfully fresh and bold meals"--